IMPACT OF DIFFERENT TILLAGE SYSTEMS ON SOIL NUTRIENT REGIME IN THE FIELD OF WINTER WHEAT AND SPRING BARLEY IN THE LEFT-BANK FOREST-STEPPE ZONE OF UKRAINE - Hanhur, V. V.; Len, O. I.; Hanhur, N. V. (Scientific Progress & Innovations, 2022)
The priority direction of modern agriculture is finding reserves to increase the yield of field crops with simultaneous improvement of soil fertility. Technological measures that can be used to achieve a real increase in soil fertility, as well as a fuller disclosure of the biological potential of crop productivity, include rational soil tillage, in particular minimal. The technology of minimal soil tillage for winter wheat (Triticum aestivum L.) and spring barley (Hordeum vulgare L.) should be taking into account the biological characteristics of crops and bioclimatic potential of the region. The aim of the research was to find the influence of different basic tillage methods on the change of nutrient regime in the fields of winter wheat and spring barley in the conditions of the Left Bank Forest-Steppe. The results of the research showed that the main tillage systems led to changes in the content of easily hydrolyzed nitrogen, mobile phosphorus and exchangeable potassium in the soil of winter wheat and spring barley fields. It was found that carrying out the minimal soil tillage, Mini-till and No-till systems for winter wheat crops, contributed to increase in the easily hydrolyzed nitrogen content in the soil layer 0-20 cm by 1.6 % 3.0 % and 2.4 % respectively, compared to classical soil tillage. In addition, there was a reverse trend in the nitrogen content in the soil layer of 20-40 cm when using minimized tillage systems relative to the classical. In the experiment it was found that according to the content of mobile phosphorus in the soil, the most pronounced was difference between the classical tillage and No-till. Studies have shown that the non-shelf tillage of soil for winter wheat increased the content of exchangeable potassium in the soil layer 0–20 cm by 1.7–6.2 %, compared with classical tillage. In the soil layer of 20–40 cm, this indicator was relatively stable in the variants of tillage options. In the experiment with spring barley, similar trends were observed in the change of nitrogen, phosphorus and potassium content in the soil layer 0–20 and 20–40 cm, as well as the distribution of these elements in the soil profile depending on the main tillage systems.